Perancangan Multimedia Interaktif Offline Bilingual Untuk Penguasaan Istilah Asing Pada Materi Public Area Di Akomodasi Perhotelan - Mubarakah, Mardliyah; Rohaeni, Neni; Ana, Ana (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2018)
This research is background by limited of student skill in mastery of foreign term. Using in intructional media of public area subject is limited, in oder to need inovative instructional media that help student. This research purpose to create interactive bilingual offline media as instructionall madia that help student to mastery foreign term of public area subject. This reearsch uses research and development by PPE model is planning, production, and evaluation. At design stage of interactive multimedia assisted with flow charts and story board to facilitate production process. The production process is carried out based on the design has been created. At this stage of the development of interactive multimedia software supporting mainly using Macromedia Flash 8. Participants in this research are two media expert to expert judgment interactive multimedia. Expert judgment for offline interactive multimedia bilingual by first media experts on feasible criteria with some suggestions for improvement. The results of the second phase of expert judgment criteria are eligible without revision after repair. Repairs carried out in accordance input from media experts. The end product of this research is a CD Interactive. Recomendation for nextÂ researcher can research of implementation in interactive bilingual offline multimedia for mastery of foreign term of public area subject or about interactive multimedia from other subject in hospitality acomofation.